Organizational Practices Generating Work Overload in the Administrative Staff of a Public Hospital and Prevalence of Burnout Symptoms - Haro Flores, Lissette Yanela (2022)
This article analyzes work overload in the administrative staff of a public hospital and its relationship with burnout syndrome. Through a mixed approach (qualitative-quantitative), nine administrative professionals are studied by means of semi-structured interviews and Maslach's questionnaire. The results reveal that the lack of personnel forces some health professionals to take on administrative tasks, especially those without job stability. A generalized tendency to burnout is observed, linked to organizational deficiencies that increase the workload and hinder the prevention of psychosocial risks. In addition, additional tasks affect performance and reduce responsiveness in their functions. The requirements of the higher level impose a high pace of work that extends beyond working hours, intensifying the overload and the risk of burnout in administrative staff.